Transcutaneous oximetry monitoring in patients with type 2 diabetes mellitus and critical limb ischemia - Olga Nikolaevna Bondarenko; N L Ayubova; Gagik Radikovich Galstyan; Ivan Ivanovich Dedov (Сахарный диабет)
Aims. To evaluate transcutaneous oximetry as a method for diagnostics and monitoring in patients with diabetes mellitus (DM) and critical limb ischemia (CLI) after percutaneous transluminal balloon angioplasty (PTBA). Materials and Methods. We enrolled 126 patients with DM and CLI for participation in this study (148 limbs in total). 22 patients underwent PTBA on both lower limbs, and 104 ? on single limb. Transcutaneous oximetry and duplex ultrasonography of lower limb arteries was performed prior to PTBA with subsequent examinations on 5-7th days, 1st, 3rd and 6th month after intervention. Transcu- taneous oxygen tension (TcpO2) was measured by Radiometer (Copenhagen) oximeter system. Duplex ultrasonography was performed on Voluson 730? Expert system (GE Medical Systems Kretztechnik GmbH&Co OHG, Austria). Results. Multiple factor analysis suggests that results of TcpO2 monitoring prior to and after PTBA are influenced by presence of ischemic heart disease, severe lower limb infections, serum creatinine, arterial hypertension and lower limb reperfusion edema. We observed a strong correlation of TcpO2 with the degree of anterior tibial artery and dorsal pedis artery occlusion. Conclusion. Transcutaneous oximetry allows evaluation of CLI severity and efficiency of PTBA in the majority oа patients with DM and CLI. Certain comorbidities impose limitations on this technique. Efficiency of endovascular intervention should be evaluated based on complex non-invasive examination, clinical data and signs of CLI.